Strategies to Prolong the Intravaginal Residence Time of Drug Delivery Systems - Esra Baloglu; Andreas Bernkop-Schnürch; Sinem Yaprak Karavana; Zeynep Ay Senyigit (Frontiers Media S.A., 2009)
The vagina has been studied as a favorable site for local and systemic delivery of drugs for female-related conditions. There are a large number of vaginal medications on the market and most of them require frequent application due to their short vaginal residence time. A prolonged vaginal residence time of formulations is therefore a key parameter for improved therapeutic efficacy. Promising approaches to prolong the residence time base on mucoadhesion, in- situ sol-gel transition and mechanical fixation. Mucoadhesive drug delivery systems can be tailored to adhere to the vaginal tissue. In-situ gelling systems offer the advantage of increased viscosity in vaginal cavity and consequently reduce outflow from the vagina. Mechanical fixation needs specially shaped drug delivery systems and reduce the frequency of administration significantly. Within this review an overview on these different strategies and systems is provided. Furthermore, the techniques to evaluate the potential of these systems for prolonged vaginal residence time are described.